2024
DOI: 10.1021/acs.langmuir.3c03914
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulations of Adsorption Behavior of Anionic Surfactants at the Portlandite–Water Interface under Sulfate and Calcium Ions

Hongxia Zhao,
Yong Yang,
Xin Shu
et al.

Abstract: The adsorption behaviors of two kinds of anionic surfactants (called HSO 4 and HPO 4 , respectively) with different negatively charged hydrophilic head groups (sulfate and phosphate groups) under different concentrations of sulfate and calcium ions at the portlandite−water interface are investigated by molecular dynamics simulations. Although the adsorption strength of HPO 4 is much greater than that of HSO 4 , the desorption energy of HSO 4 is slightly greater at an early stage of desorption due to a more per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Acetonitrile was modeled using a flexible six-site potential model introduced by Kowsari and Tohidifar . The LJ parameters for BnBr, TBA + , and I – were taken from the literature. The van der Waals interactions of the solute with Au (111) were represented by Lennard-Jones potential described by Heinz et al Several studies have demonstrated that these parameters can qualitatively replicate interactions between the metal surface and the solution interface, , while the Lennard-Jones parameters for interactions in solution effectively capture physical phenomena in the bulk.…”
Section: Methodsmentioning
confidence: 99%
“…Acetonitrile was modeled using a flexible six-site potential model introduced by Kowsari and Tohidifar . The LJ parameters for BnBr, TBA + , and I – were taken from the literature. The van der Waals interactions of the solute with Au (111) were represented by Lennard-Jones potential described by Heinz et al Several studies have demonstrated that these parameters can qualitatively replicate interactions between the metal surface and the solution interface, , while the Lennard-Jones parameters for interactions in solution effectively capture physical phenomena in the bulk.…”
Section: Methodsmentioning
confidence: 99%